Pengaruh Kompetensi dan Kompensasi Terhadap Kinerja Pegawai - A. Fauzan Fadlan fauzan; Hotler Epindo Lumban Gaol (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Research Objectives: To find out partially and simultaneously the effect of competence and compensation on the performance of employees of the North Jakarta Transportation Service Parking Service Unit. Research Methods: Data collection instruments were obtained through distributing questionnaires to respondents using google form. The data collection technique of the research sample was using the random sampling method, namely simple random sampling. The results of the study: that partial competence has an effect on employee performance. Compensation partially affects employee performance. Competence and compensation simultaneously affect employee performance. The influence of competence and compensation on employee performance is 56.9% and the remaining 43.1% is influenced by other variables.